Commonwealth Caribbean in the New World Order : between Europe and North America? - PAYNE, Anthony J. (1992)
Argues that no other arrangement open to the Commonwealth Caribbean offers near the magnitude of threats or opportunities that arise from the Single European Market or NAFTA. Considers the relations between Europe and the Caribbean and between North America and the Caribbean.